An Empirical Analysis of The Impact of Islamic Banking on Real Output in Indonesia - Sasana, Hadi; Ramdani, Deni; Novitaningtyas, Ivo (Economica: Jurnal Ekonomi Islam, 2020)
Abstract: The role and contribution of Islamic finance on economic growth in Indonesia has increased gradually and steadily. This is because the Islamic economy's universal and comprehensively basic principle is the primary foundation of Islamic banking. This research aimed to analyze the role of Islamic Banking on Indonesia's real sector during 2007.01 – 2016.04. This study used the Vector Error Correction Model (VECM) as a tool to analyze secondary data. The result showed that in Indonesia, sharia deposit positively and significantly influenced actual output in the short term. In addition, in the long-term, sharia financing positively and significantly influenced actual output. Moreover, Granger Causality Test proved the occurrence of one-way causality between actual output and inflation. Thus, Islamic banking can encourage actual output in Indonesia. The results of this study become a consideration for stakeholders and policymakers to pay more attention to strategies and policies that support economic growth in Indonesia.Abstrak: Perkembangan keuangan syariah di Indonesia semakin meningkat setiap tahunnya. Prinsip-prinsip dasar ekonomi syariah yang universal dan komprehensif merupakan landasan utama perbankan syariah. Tujuan penelitian ini untuk menginvestigasi peran perbankan syariah terhadap sektor riil di Indonesia selama periode 2007.01 – 2016.04. Penelitian ini menggunakan Vector Error Correction Model (VECM) sebagai alat untuk menganalisis data sekunder. Hasil penelitian menemukan bahwa dalam jangka pendek deposito syariah berpengaruh positif dan signifikan terhadap output rill. Selain itu, dalam jangka panjang pembiayaan syariah berpengaruh positif dan signifikan terhadap output riil di Indonesia. Lebih lanjut, Uji Kausalitas Granger membuktikan terjadinya kausalitas satu arah antara output riil dan inflasi. Dengan demikian, perbankan syariah mampu mendorong output riil di Indonesia. Hasil penelitian ini menjadi bahan pertimbangan bagi para pemangku kepentingan dan pengambil kebijakan untuk lebih memperhatikan strategi dan kebijakan yang mendukung pertumbuhan ekonomi di Indonesia.